A threat to property and lives: Black ‘crime’ and white ‘victims’ in Krugersdorp, 1887 to 1914 - Dugmore, Charles (My University, 1991)
"Although he was helpless and defenceless, he decided to declare 'war' against his persecutors. Without arms he said, he was going to wage a relentless struggle against the white man. He was going to rob him, break into his stores, burgle his houses, and make him uncomfortable in every way possible". (1) A common perception amongst white residents in Krugersdorp during the period 1837-1923, was that blacks were engaged in a kind of low-key war against whites where newspapers reported almost every other day, how a white storekeeper had been murdered and robbed, how a white girl had been brutally raped, how gangs of 'Amalaita' were attacking white men in the streets and how even the policemen were not invulnerable to assaults at the hands of black criminals. What this Paper intends to show is that Krugersdorp's white residents saw hardened black criminals as a "threat to property and lives", and while calling for more police, more secure prisons and harsher sentences on such criminals, developed a racist consciousness that turned all blacks into "ascriptive criminals" who had to be separated from whites in every possible sphere and 'incarcerated' into-mine compounds, locations, separate hospitals, schools and halls and into separate queues at market tables, railway ticket offices and post offices, removed off the sidewalks and out of parks. In the process,this Paper hopes also to demonstrate the injustice of such a racist perception amongst white residents, the different ways in which black criminal statistics were inflated, the perceptions of black criminals themselves, the views of black residents of Krugersdorp, and finally, the minority voice amongst whites that responded differently to black crime. Rather than waste valuable space on a detailed "background" to introduce this Paper, I have taken the liberty to include a detailed survey of Krugersdorp within the text as a whole. The Paper progresses roughly chronologically from 1887 to 1914.
African Studies Seminar series. Paper presented May, 1991
Keywords: Crime. South Africa. History